A Systematic Review and Meta-Analysis of the Outcomes of Laparoscopic Cholecystectomy Compared to the Open Procedure in Patients with Gallbladder Disease - Debajit Kumar Roy; Rahaman Sheikh (Avicenna Journal of Medicine, 2024)
Background Conflicting evidence regarding the laparoscopic versus open cholecystectomy outcomes in scientific literature impacts the medical decision-making for patients with gallbladder disease. This study aimed to compare a range of primary and secondary outcomes between patients receiving laparoscopic cholecystectomy and those with open intervention.